Ethics in Hospitality. Toward a Deontological Code for the Development of Sustainable Tourism through Governance - Valero Quezada, Ana María (2023)
The objective of this study is to define a deontological code by presenting the precepts discussed in meetings,assemblies, and global tourism summits for analysis and synthesis. The methodology employed is contentanalysis, involving a literature review on the topic. Inventory techniques and tools such as checklists, exclusion lists, and information weighting were chosen. The primary source documents analyzed include: The Club of Rome Report, United Nations Environment Programme, Brundtland Report, Sustainable Tourism Charter, Global Code of Ethics for Tourism, and The Responsible Tourist. A synthesis is presented in inventory lists along with a comparison of the analyzed documents and their precepts. Furthermore, the principles, codes, and recommendations found in the selected documents are developed for review and analysis. Additionally, various recommendations are weighted to integrate the analyzed elements into a deontological code that serves as a practical precedent for theoretical foundations. The ethical participation of all stakeholders in tourism management at destinations is observed to ensure that sustainable tourism development programs implement governance principles.